Early and short‐term intensive management after discharge for patients hospitalized with acute heart failure: a randomized study (ECAD‐HF). (21st October 2021) - Logeart, Damien; Berthelot, Emmannuelle; Bihry, Nicolas; Eschalier, Romain; Salvat, Muriel; Garcon, Philippe; Eicher, Jean‐Christophe; Cohen, Ariel; Tartiere, Jean‐Michel; Samadi, Alireza; Donal, Erwan; deGroote, Pascal; et al.
Abstract: Aims: Hospitalization for acute heart failure (HF) is followed by a vulnerable time with increased risk of readmission or death, thus requiring particular attention after discharge. In this study, we examined the impact of intensive, early follow‐up among patients at high readmission risk at discharge after treatment for acute HF. Methods and results: Hospitalized acute HF patients were included with at least one of the following: previous acute HF < 6 months, systolic blood pressure ≤ 110 mmHg, creatininaemia ≥ 180 µmol/L, or B‐type natriuretic peptide ≥ 350 pg/mL or N‐terminal pro B‐type natriuretic peptide ≥ 2200 pg/mL. Patients were randomized to either optimized care and education with serial consultations with HF specialist and dietician during the first 2–3 weeks, or to standard post‐discharge care according to guidelines. The primary endpoint was all‐cause death or first unplanned hospitalization during 6‐month follow‐up. Among 482 randomized patients (median age 77 and median left ventricular ejection fraction 35%), 224 were hospitalized or died. In the intensive group, loop diuretics (46%), beta‐blockers (49%), angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers (39%) and mineralocorticoid receptor antagonists (47%) were titrated. No difference was observed between groups for the primary endpoint (hazard ratio 0.97; 95% confidence interval 0.74–1.26), nor for mortality at 6 or 12 months or unplanned HF rehospitalization. Additionally, no difference between groups according to age, previous HF and left ventricular ejection fraction was found. Conclusions: In high‐risk HF, intensive follow‐up early post‐discharge did not improve outcomes. This vulnerable post‐discharge time requires further studies to clarify useful transitional care services.